(untitled) (Sociología y tecnociencia, 2020)
In Mexico there are very few public universities that obtain patent certificates and extremely few of those make it to the business sector. The objective of this document is to describe and explain the case of the licensing of an academic patent, applying as a theoretical-conceptual framework the Field Theory of Pierre Bourdieu. The analysis focuses on the differentiation of perspectives and interests between the actors involved: the inventor, the licensing university and the licensee entrepreneur. In the end, the social impact of scientific inventions (such as the one presented here) when they